Male predisposition to severe COVID-19: Review of evidence and potential therapeutic prospects (2020)
The severe form of COVID-19 has significant sex disparities, with high fatalities commonly reported among males than females. The incidence of COVID-19 has also been higher in males compared with their female counterparts. This trend could be attributed to a better responsive and robust immune system in females. Cytokine storm is one of the pathophysiological features of severe COVID-19, and it occurs as a result of over-activation of immune cells leading to severe inflammation and tissue damage. Nevertheless, it is well modulated in females compared to their male counterparts. Severe inflammation in males is reported to facilitate progression of mild to severe COVID-19. The sex hormones, estrogens and androgens which exist in varying functional levels respectively in females and males are cited as the underlying cause for the differential immune response to COVID-19. Evidence abounds that estrogen modulate the immune system to protect females from severe inflammation and for that matter severe COVID-19. On the contrary, androgen has been implicated in over-activation of immune cells, cytokine storm and the attendant severe inflammation, which perhaps predispose males to severe COVID-19. In this review efforts are made to expand understanding and explain the possible roles of the immune system, the sex hormones and the angiotensin-converting enzyme (ACE) systems in male bias to severe COVID-19. Also, this review explores possible therapeutic avenues including androgen deprivation therapy (ADT), estrogen-based therapy, and ACE inhibitors for consideration in the fight against COVID-19.